PENGARUH PERBANDINGAN TEPUNG KETAN PUTIH DENGAN TEPUNG KACANG MERAH (Phaseolus vulgaris L.) TERHADAP KARAKTERISTIK TEMERODOK - Hs, Intan Azizah; Yusa, Ni Made; Wiadnyani, A.A. Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPA, 2020)
The purpose of the study was to find the optimum ratio of glutinous rice flour and red kidney bean flour ( Phaseolus vulgaris L.) to produce temerodok with the best characteristics. The completely randomized design (CRD) was used in the research with treatment that is the ratio of glutinous rice flour with red kidney bean flour which consists of 6 levels: 100%:0%,90%:10%, 80%:20%, 70%:30%, 60%:40%, 50%:50%. The treatment was repeated 3 times to obtain 18 units of the experiment. The data obtained were analyzed by variance and if the treatment had an effect on the observed variable then continued with the Duncan Multiple Range Test (DMRT) test.The ratio of glutinous rice flour and red kidney beans flour has a very significant effect on water content, ash content, protein content, fat content, carbohydrate content, color (scoring), texture (hedonic and scoring), taste (scoring) and significant effect against the levels of crude fiber, color (hedonic), taste (hedonic) and overall acceptance (hedonic). The ratio of glutinous red kidney bean flour (50%: 50%) produces the best characteristic temerodok based on the matrix table, namely: water content 5.49%, 2.53% ash content, 15.19% protein content, fat content 15.46%, 61.31% carbohydrate content, crude fiber content 5.54%, brown color, hard texture, taste very red beans, color, texture, taste and overall acceptancered kidney bean taste and neutral color, texture, taste and and overall acceptability. Keywords : Tradisional food,temerodok, red kidney bean flour,glutinous rice flour.